Effect of periodic ventilation in a classroom on air quality and microclimate - D. S. Simonov; A. Yu. Morozov; K. D. Konovalova; E. L. Miskova (Архитектура, строительство, транспорт)
Air quality and microclimate parameters in classrooms impact student health and academic performance. Calculate the precise reduction in carbon dioxide concentration achieved through periodic ventilation is challenging. Therefore, an experimental study was conducted to evaluate the effect of ventilation on air quality and microclimate parameters during the cold season. The research object was a classroom with an area of 55.6 m2. On the first day of the study, ventilation was implemented before the start of classes and during breaks. On the second and third days, the ventilation schedule was determined by the students and lecturers. Carbon dioxide concentration, air temperature and relative humidity were measured using an air quality meter positioned in the center of the room at a height of 1.5 meters. On the first day, the air quality met the required standard for 16% of the teaching time, while it was acceptable and low for 47 and 37% of the time, respectively. The maximum carbon dioxide concentration reached 2639 ppm, and an unstable thermal environment was observed, with a maximum temperature increase of 4.7 °C over a 45-minute class period. Without control over the ventilation schedule and with the classroom door closed during classes, the duration of study time with poor air quality increased by 2.2 times, and the maximum carbon dioxide concentration was 1.3 times higher.